(untitled) (Baghdad Science Journal, 2014)
The present study was included the isolation of Keratinophilic fungi from water samples taken from 19 indoor public swimming pools in Baghdad during four season (summer ,fall ,spring ,and winter). Isolation period was September 2011and September 2012 . Samples were collected from different places in swimming pool . Sixteen keratinophilic fungal species, belonging to twenty –one genera were isolated using Surface Dilution Plating (SDP) and Hair Bait Technique (HBT) . Aspergillus genus was the most frequent and occurrence (19.84%), followed by Trichophyton (11.60%) and Fusarium (7.59% ) . The most common fungal infection occurred in summer season (42.16%) , and the most frequent month manifestation of species occurred in August (17%) .